Answer:
The anwser is 10.4
Step-by-step explanation:
0.5(20)+0.4
Answer: -7x3 + 13x2 + 9x - 12
Answer:
3(5x2+2x-4)-x7x2+2x-3)
15 x 6 + 6x -12 - x7 + x2 + 2x -3
90 + 6x - 12 - x7 + x2 + 2x -3
(6x + 2x) (+90 - 12 - 3) (-x7 + x2)
8x + 75 - x5
Answer:
9π cm - exact value
28.26 cm - approximate value
Step-by-step explanation:
C = πd =9π cm - exact value
or
C=9π≈ 28.26 cm - approximate value
Answer:60
Step-by-step explanation:
B)False
B. 125.7 ft.2
C. 241.6 ft.2
D. 103.3 ft.2
Answer:
Answer: 241.6 ft² (Answer C)
Step-by-step explanation:
2.8y + 6 + 0.2y = 5y – 14
Answer:
Step-by-step explanation:
Simplifying
2.8y + 6 + 0.2y = 5y + -14
Reorder the terms:
6 + 2.8y + 0.2y = 5y + -14
Combine like terms: 2.8y + 0.2y = 3y
6 + 3y = 5y + -14
Reorder the terms:
6 + 3y = -14 + 5y
Solving
6 + 3y = -14 + 5y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-5y' to each side of the equation.
6 + 3y + -5y = -14 + 5y + -5y
Combine like terms: 3y + -5y = -2y
6 + -2y = -14 + 5y + -5y
Combine like terms: 5y + -5y = 0
6 + -2y = -14 + 0
6 + -2y = -14
Add '-6' to each side of the equation.
6 + -6 + -2y = -14 + -6
Combine like terms: 6 + -6 = 0
0 + -2y = -14 + -6
-2y = -14 + -6
Combine like terms: -14 + -6 = -20
-2y = -20
Divide each side by '-2'.
y = 10
Simplifying
y = 10
Answer:
y= 11
Step-by-step explanation:
we have:
2.8y + 6 + 0.2y = 5y – 14
or 3y + 6 = 5y -14
and 3y + 6 - 6 = 5y -16 -6
and 3y = 5y -22
and 3y - 5y = -5y +5y -22
so -2y = -22
finally y = -22/-2
or y=11
Hope that useful for you.